HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DAN KOORDINASI MATA DAN TANGAN DENGAN AKURASI SERVIS ATAS TIM VOLI SMP NEGERI 6 BAGAN SENEMBAH ROKAN HILIR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the relationship of wrist flexion with free throw results, hand eye coordination with free throw results and wrist flexion and eye-hand coordination with free throw results on the Libas Club Teluk Kuantan basketball team. Some of the problems that occur include, the player can already shoot, but when doing free throws the power given is too strong which causes the ball not to enter, bouncing because it touches the reflection board. The type of research used is the type of correlation research, this research is a correlational study by comparing the measurement results of three different variables in order to find the level of relationship between these variables. The population in this study amounted to 12 people who came from the Taluk Kuantan Libas team. Because in this study using a total sampling technique is a sampling technique where the number of samples is equal to the total population. The instruments used in this study were a wrist flexing test, a ball throwing test, and a free throw ball test. Then the data test using the normality test, normality test data with liliefors test, correlation analysis. The variable normality test X1 L₀max (0.139) <Ltable (0.242), the variable normality test X2 L₀max (0, 180) <Ltable (0.242), the normality test variable Y L₀max (0, 142) <Ltable (0.242). With that the data is normally distributed and the conclusions of the research show that the hypothesis is accepted at a significant level α = 0.05 in other words there is a relationship between flexibility, coordination of free throws on the Libas Taluk kuantan basketball team with a rcount (0.940)> rtable (0.602).Key Words: Wrist Speculation, Hand Eye Coordination, Free Throw, Basketball